A National Health Service (letter) - Roberts, Bryn, 1897-1964
1944-06-06 1944 1940s 2 pages Without the application of the modest reforms referred to above, the Union believes that an efficient National Health Service is unattainable. Yours sincerely, Bryn Roberts GENERAL SECRETARY. 292/847/2/59